Faktor-Faktor Yang Mempengaruhi Penyerapan Tenaga Kerja Pada Industri Pengolahan Kayu di Kabupaten Langkat - Gultom, Juliana Frisca; Mardiana, Siti; Ginting, Rahmanta (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2020)
This research was conducted for two months from April 2015 to June 2015 in Langkat District, known as one of the centers of the wood processing industry in North Sumatra. The object of research is entrepreneurs in wood industry companies in the study area. Based on the problems that have been formulated, the study aims to: (1) Analyze the effect of working capital variables, wood raw materials, labor costs and productivity in the wood processing industry on labor absorption in Langkat Regency. (2) Analyzing the average size of processed wood production produced by companies in Langkat Regency. (3) Analyzing the amount of the average absorption of labor per month received by the company in Langkat Regency. The study area was determined purposively with a sample size and population of 25 companies. Sampling of respondents using simple random sampling. The data used are primary data and secondary data. To examine the relationship between income and production costs the multiple linear regression analysis model is used. The results of this study indicate that the variable amount of working capital, wood raw materials, labor wages and productivity in the wood processing industry on labor absorption in Langkat District is 374 people with an average of 15 people, the average size of processed wood production produced the company in Langkat Regency is 282,429 m3. And the average absorption of labor per month received by the company in Langkat Regency is 15 people.